The rough guide to Cambodia - Boyle, Emma (Rough Guide to ..., 2017)
This in-depth coverage of Cambodia's local attractions, sights, and restaurants takes you to the most rewarding spots-from the ornate temple of Angkor Wat to the amazing street food of Phnom Penh to the gorgeous beaches of Sihanoukville-and stunning color photography brings the nation to life. The locally based Rough Guides author team introduces the best places to stop and explore, and provides reliable insider tips on topics such as driving the roads, taking walking tours, or visiting local landmarks. You'll find special coverage of history, art, architecture, and literature, and detailed information on the best markets and shopping for each area in this fascinating country. The Rough Guide to Cambodia also unearths the best restaurants, nightlife, and places to stay, from backpacker hostels to beachfront villas and boutique hotels, and color-coded maps feature every sight and listing. Make the most of your time with The Rough Guide to Cambodia.